KUALITAS PELAYANAN KARTU TANDA PENDUDUK ELEKTRONIK (KTP-El) DI KECAMATAN BANYUASIN KABUPATEN BANYUASIN - Deffi Haryani (Wacana: Jurnal Ilmu Sosial dan Ilmu Politik Interdisiplin, 2024)
The aim of this research is to find out the quality of the National Identity Card (KTP) service at the Banyuasin District Office, Banyuasin Regency. This research is located in Banyuasin District, with the unit of analysis being the people of Banyuasin District who have or are currently making Resident Identity Cards (KTP). The method used in this research is qualitative method. Research methods are basically a scientific way to obtain data with specific purposes and uses. This research uses a survey method. The type of data consists of primary data obtained through interviews and direct observation in the field, while secondary data comes from report documents, regulations relating to the problem to be studied. The results of this research show that in general the service for making identity cards (KTP) in Banyuasin District, seen from the five dimensions of service, namely reliability, responsiveness, confidence, attention and tangibles, based on research, can be said to be good.